Synthesis of a nanoparticle system for the enhanced accumulation of fluorescently-labelled amino acids encapsulated in monodispersed chitosan nanoparticle system - Ummu Afiqah Hassan,; Mohd Zobir Hussein,; Mas Jaffri Masarudin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Poor in vivo bioavailability of nutrient is a major challenge in efficient delivery of nutraceutics. The increased bioavailability of nutraceuticals is prerequisite for efficient absorption by the gastrointestinal system. Nanotechnology-based approaches for nutraceutical applications could potentially increase absorption of nutrients and enhance its cellular accumulation due to its nanosize and promote better in vivo energy biodistribution. However, the dynamics of intracellular cell trafficking of nanoparticles and nutraceutical release has remain scarcely studied. This study describes a non-efficacious nanoparticle-mediated system for the encapsulation and delivery of fluorescently-labelled amino acids using tripolyphosphate as a crosslinker. Light scattering data showed successful formation of particle size as small as 65.69 nm with low polydispersity index (PDI) value of 0.178 at specific volume ratios of chitosan to tripolyphosphate. Following encapsulation, nanoparticle size and PDI value increased to 182.73 nm and 0.257 respectively discern successful accommodation of the fluorescently-labelled amino acid within its core. In vitro visualization of amino acids release and accumulation via fluorescence microscopy suggested that encapsulated amino acids were efficiently accumulated into Vero3 cell cytoplasm at 24 hours post treatment with localization in proximity to the cell nucleus. These results therefore suggested that the chitosan nanoparticle system developed was able to enhance the intracellular accumulation of glutamic acids and may serve as a suitable carrier for nutraceuticals delivery.